Risk factors for severe outcomes in Extended-Spectrum Beta-Lactamase (ESBL) Bacteremia: a single-center study - Muhammad Hazwan N,; Najma Kori,; Ramliza Ramli,; Rozita Hod,; Chee LI,; Petrick @ Ramesh K. Periyasamy, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Expanded-spectrum beta-lactamase (ESBL) bacteremia often leads to severe outcomes like mortality and treatment failure. This study aimed to identify risk factors in patients with ESBL bacteremia. A retrospective cohort analysis was conducted among patients aged 13 years and above who were admitted to Hospital Canselor Tuanku Muhriz (HCTM) due to ESBL bacteremia between the period of January 2015 and August 2019. Patients with polymicrobial bacteremia were excluded. The all-cause in HCTM mortality rate was 30.2%, while the infection-related mortality rate was 22.5%. The risk factors of all-cause in-hospital mortality include hypertension, diabetes mellitus, skin and soft tissue infections (SSTIs), urinary catheterisation and mechanical ventilation. The independent risk factor associated with mortality was mechanical ventilation (AOR 3.12; CI 1.06- 9.18; p = 0.04). No association found between appropriate empirical antibiotic treatment with mortality (p = 0.74), treatment success (p = 0.71) or length of hospital stay (p = 0.84). However, appropriate definitive treatment was associated with a lower mortality rate (p<0.01) and higher treatment success (p<0.01). Mechanical ventilation was the only independent risk factor significantly associated with mortality, while appropriate definitive treatment was associated with a lower mortality rate and higher treatment success.